Bridging Neuromarketing and Data Analytics in Tourism: An Adaptive Digital Marketing Framework for Hotels and Destinations - Thomas Krabokoukis (Tourism and Hospitality)
This study proposes the Tourism Adaptable Digital Marketing Framework (TADMF), a flexible, cyclical model tailored to optimize digital marketing strategies for hotels and destinations. By leveraging data-driven insights and neuromarketing principles, the framework addresses critical gaps in traditional linear models to maximize bookings for hotels and enhance awareness of destinations. The three-stage cyclical process, attraction, engagement, and conversion, ensures continuous feedback and refinement across the customer journey. Hotels benefit from tailored techniques, such as dynamic pricing and personalized recommendations, while destinations focus on storytelling and user-generated content to forge emotional connections. Compared to traditional marketing models, this framework uniquely integrates online and offline interactions to create cohesive customer experiences. Key findings reveal that the TADMF fosters a dynamic interplay between theoretical innovation and practical applicability, demonstrating scalability and adaptability to diverse tourism contexts. The study concludes that the TADMF offers a robust foundation for addressing the evolving challenges of digital marketing in tourism, paving the way for future research into advanced technologies such as AR, VR, and AI.